2008
DOI: 10.1590/s0004-27492008000100025
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Alcaligenes xylosoxidans endophthalmitis: report of two cases

Abstract: We report two cases of postoperative Alcaligenes xylosoxidans endophthalmitis. A 78-year-old woman in good general health developed A. xylosoxidans endophthalmitis one month after an uncomplicated phacoemulsification procedure with posterior chamber intraocular lens. It was performed on her left eye, at another institution. Removal of the intraocular lens and capsule was performed because of recurrent inflammation after vitrectomy and intravitreal antibiotic injections. Her son, a 55-year-old man, developed A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Although postcataract endophthalmitis is a rare complication associated with cataract surgery, it is one of the most devastating ocular diseases, and can severely impact the patient's quality of life. Achromobacter xylosoxidans , a rare cause of postcataract endophthalmitis, flourishes in humid environments, and is often resistant to conventional antibiotics and surgical treatment [ 1 2 3 4 ]. We report five recalcitrant, chronic, and recurrent cases of endophthalmitis caused by A. xylosoxidans .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although postcataract endophthalmitis is a rare complication associated with cataract surgery, it is one of the most devastating ocular diseases, and can severely impact the patient's quality of life. Achromobacter xylosoxidans , a rare cause of postcataract endophthalmitis, flourishes in humid environments, and is often resistant to conventional antibiotics and surgical treatment [ 1 2 3 4 ]. We report five recalcitrant, chronic, and recurrent cases of endophthalmitis caused by A. xylosoxidans .…”
mentioning
confidence: 99%
“…Villegas et al [ 3 ] presented histological evidence of A. xylosoxidans on the lens capsule; which can remain in the capsular bag and on the intraocular lens. Donlan and Costerton [ 5 ] reported that A. xylosoxidans creates a biofilm to survive in a toxic environment, suggesting that complete intraocular lens and lens capsule removal are essential for preventing recurrence of A. xylosoxidans infections [ 1 2 3 4 ]. In case 1, endophthalmitis recurred in the presence of the remnant lens capsule after intraocular lens removal and capsular cut by ocutome, using a scleral depressor ( Fig.…”
mentioning
confidence: 99%
“…Mortality is high in immunocompromised patients with invasive infections [2]. Clinical presentations are diverse, including life-threatening infections such as endocarditis [3,[4][5][6][7]. Our first case documents a novel presentation of an infected pancreatic pseudocyst in an immunocompetant adult by A. xylosoxidans, while the second case involves a wound infection acquired nosocomially from contaminated wound dressings.…”
Section: Discussionmentioning
confidence: 87%
“…Most infections are acquired during hospitalisation, with primary uncomplicated bacteremia, catheter-associated infections, and pneumonia being the common clinical presentations [3]. Other infections such as post-operative infections of the eye, meningitis, endocarditis and hepatobiliary infections are also reported [4][5][6][7]. We present two unique cases: in the first, Achromobacter xylosoxidans caused an infection leading to a pancreatic pseudocyst in an adult immunocompetant man.…”
Section: Introductionmentioning
confidence: 94%
“…A. xylosoxidans is a common fluid contaminant [9]. This organism is also part of the normal flora of the ear and gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%